The European COvid Survey (ECOS): Technical report - Iryna Sabat; Sebastian Neumann-Böhme; Tom Stargardt; Jonas Schreyögg (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2024)
European COvid Survey (ECOS), a longitudinal study spanning eight European countries, was initiated early in the COVID-19 pandemic. Its purpose was to comprehend public perceptions, trust, knowledge, and behaviors related to COVID-19, including vaccination. The study aimed to enable timely monitoring and assess relationships between these variables, producing evidence for policy and research in Europe. ECOS pursued a dual objective: first, conducting quick descriptive analyses at the end of fieldwork to produce policy-relevant evidence and share timely findings on sentiments toward containment policies, vaccinations, and vaccine types through press releases and events. These findings were valuable as they were both prompt and representative of national populations. Second, ECOS aimed to address health-economic research questions for an academic audience, utilizing advanced analytic methodologies. The resulting data-based research from ECOS provided an empirical foundation to understand longitudinal phenomena and relationships, contributing to a deeper comprehension of socioeconomic processes and behaviors during the COVID-19 pandemic. Importantly, it offered informed findings for policymakers to shape effective responses and policies. This technical report provides an account of the design, development, and methodology of 11 data collections henceforth referred to as waves of the survey, which were fielded between April 2020 and December 2022.
Keywords: 330; Covid-19; longitudinal survey; health economics; trust; vaccination; policy support